Renewable Energies as a Future Strategic Trend to achieving the Environmental Sustainability: Solar energy and Wind energy as a model - BENAZZA HANAA (Journal of North African Economies, 2025)
In light of the increasing global demand for energy, with the possibility of depletion of these traditional energies on the one hand, and in light of the increasing deterioration of environmental systems as a result of the accumulation of waste and the increase in toxic gas emissions on the other hand, the energy transition has become a major trend in the modern world, and the supply of renewable, clean and safe energy has become a must to achieve the dimensions of sustainable development, especially the environmental dimension. In this context, the current study aimed to highlight the role of these renewable energies as inexhaustible and environmentally friendly in achieving environmental sustainability, by focusing on solar energy and wind energy as a cornerstone. Both solar and wind energy are growing rapidly, which can contribute significantly to achieving goals set by many countries to reduce greenhouse gas emissions, as these energies were responsible for more than 10% of global electricity for the first time in the past year.